Identification of Flap Motion Parameters for Vibration Reduction in Helicopter Rotors with Multiple Active Trailing Edge Flaps - Uğbreve;ur Dalli; Şcedilefaatdin Yüksel (Shock and Vibration)
An active control method utilizing the multiple trailing edge flap configuration for rotorcraft vibration suppression and blade loads control is presented. A comprehensive model for rotor blade with active trailing edge flaps is used to calculate the vibration characteristics, natural frequencies and mode shapes of any complex composite helicopter rotor blade. A computer program is developed to calculate the system response, rotor blade root forces and moments under aerodynamic forcing conditions. Rotor blade system response is calculated using the proposed solution method and the developed program depending on any structural and aerodynamic properties of rotor blades, structural properties of trailing edge flaps and properties of trailing edge flap actuator inputs. Rotor blade loads are determined first on a nominal rotor blade without multiple active trailing edge flaps and then the effects of the active flap motions on the existing rotor blade loads are investigated. Multiple active trailing edge flaps are controlled by using open loop controllers to identify the effects of the actuator signal output properties such as frequency, amplitude and phase on the system response. Effects of using multiple trailing edge flaps on controlling rotor blade vibrations are investigated and some design criteria are determined for the design of trailing edge flap controller that will provide actuator signal outputs to minimize the rotor blade root loads. It is calculated that using the developed active trailing edge rotor blade model, helicopter rotor blade vibrations can be reduced up to 36% of the nominal rotor blade vibrations.